Automatic shaking table device of simple and easy baby of intelligence - ZUO YI; LIU ZHIHUA; LIU QINGHUA; LUO GUOLIANG; WANG YUAN; HUANG MINGHE; KE FENFEN; CAO YUANLONG; YI YUGEN (2017)
The utility model provides an one side is equipped with the plastics cam, and the plastics cam passes through the derailleur and connects the motor, and motor connection director, controller connect the time -recorder respectively that automatic shaking table device of simple and easy baby of intelligence, the arc foot of shaking table and a bed end department that vibration sensor, vibration sensor place at the shaking table. The utility model has the beneficial effects of: simple structure, convenient to use, according to the height of the altitude mixture control pouring weight base of the arc foot of shaking table, start control ware, perception motor to the vibration of rocking bed after rotates and drives the plastics cam and rotate again to make the shaking table wave automatically, and the time -recorder timing, time to back motor automatic shutdown. 种智能简易婴儿自动摇床装置，摇床的弧形脚的侧设有塑料凸轮，塑料凸轮通过变速器连接电机，电机连接控制器，控制器分别连接计时器和振动传感器，振动传感器放置在摇床的床底处。本实用新型的技术效果是：结构简单，便于使用，根据摇床的弧形脚的高度调节重块底座的高度，启动控制器，再感知到摇床振动后电机转动带动塑料凸轮转动